WAKF OF MONEY IN SHARIA ECONOMIC LAW PERSPECTIVE: Study of Human Resource Management in Indonesian Waqf Savings Dompet Dhuafa - M. Munawwir Al-Qosimi; A Amrin; Didin Saepudin (Profetika: Jurnal Studi Islam, 2022)
This study aims to determine cash waqf from the perspective of sharia economic law by focusing on human resource management in Indonesian waqf savings wallets for the poor. This study uses a qualitative research type with a field study on the Indonesian Waqf Savings of Dompet Dhuafa Republika in Ciputat Indah Permai with an approach descriptive analysis. The data collection techniques are interviews, documentation, and observation. The data analysis uses data reduction, compiling categories, and synthesizing by inductive analysis. The results showed that human Resource Management implemented by TWI is by sharia, both in planning, recruitment, nazir selection, training, development, supervision, performance appraisal, and employee compensation. To create good corporate governance in the management of cash waqf, TWI should have a System Procedure. Because to measure the performance of cash waqf management, of course, it is guided by the operational standards that have been set.